PERLINDUNGAN TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM (ABH) MELALUI PEMBIMBING KEMASYARAKATAN - Adrian Sofyan (Lembaga Penelitian Universitas Langlangbuana, 2020)
Law of the Republic of Indonesia No. 3 of 1997 on Children's Justice, in 2012 was replaced with Law of the Republic of Indonesia No. 11 of 2012 on the Child Criminal Justice System, this brought fresh wind to the legal problems faced by children. It is hoped that with the presence of Law Number 11 of 2012 can help solve various problems of children facing the law, which increasingly, increasing with a wide range of cases. Correctional Center which is a correctional technical implementation unit that carries out the duties and functions of community research, mentoring, supervision, and mentoring